2009
DOI: 10.1017/s1368980009991236
|View full text |Cite
|
Sign up to set email alerts
|

Severe tooth loss in older adults as a key indicator of compromised dietary quality

Abstract: Objective: Poor oral health influences the dietary quality of older individuals. The objective of the present study was to relate the number of teeth to adherence to the 2005 Dietary Guidelines for Americans among an ethnically diverse sample of older adults. Design: A block cluster design was used to obtain a sample of older adults. Data were weighted to census data for ethnicity and gender. Dietary intakes were assessed using an FFQ and converted into Healthy Eating Index-2005 (HEI-2005) scores. Setting: Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 39 publications
(67 reference statements)
6
67
1
3
Order By: Relevance
“…Corroborating findings of the present study, other studies found lower BHEI score [22] in edentulous older adults [13] and in those with oral cavity problems [22] and reported that oral health is a major factor affecting diet quality [23] of older adults.…”
Section: Discussionsupporting
confidence: 89%
“…Corroborating findings of the present study, other studies found lower BHEI score [22] in edentulous older adults [13] and in those with oral cavity problems [22] and reported that oral health is a major factor affecting diet quality [23] of older adults.…”
Section: Discussionsupporting
confidence: 89%
“…Unlike previous applications of HEI-2005 that simply focus on total and component scores (10)(11)(12)(13) , the current unique investigation of top dietary sources contributing to HEI-2005 components provides insight into strategies and messages that could improve the diet quality and health of a region. Although some messages are appropriate for the entire LMD population, others may be more appropriate for specific demographic groups.…”
Section: When Examining Total and Component Hei-2005 Scoresmentioning
confidence: 99%
“…, Savoca et al . ) and the adverse effects of edentulism on health have been well substantiated (Brown ). However, no previous studies have compared adverse outcomes of edentulism to saving teeth by root canal treatment.…”
Section: Introductionmentioning
confidence: 98%